Geographic, Natural, Social, Economic and Administrative Cases of Yozgat Sanjak with District of Akdagmadeni and Bogazlıyan at the Beginning of the 20th Century - Mumyakmaz, Hatice Guzel (Fırat University, 2020)
This sudy aims to reveal the geograpihical, natural, social, economic and adminstrative status of the Yozgat Sanjak of the Ankara Province at the begining of the 20th Century and the two major districts of Bogazlıyan and Akdagmadeni. In this context, the main source of the study is the 1325 numbered Ankara Province Yearbook and the documents in the Ottoman and Republican Archives. Besides some research works related to history of Yozgat will be utilized. In this study, It was noted that Yozgat had almost smiliar geographical and natural features to present day. Although the majority of the population consist of Muslims, the non Muslims population is found both in the center and in the two center and in the two districts of Salname. The Greek population is more dominant especially in Akdağmadeni region. The economic status of the Yozgat Sanjak’s and districts was recorded on taxes and cereals and livestocks. Especially in Akdagmadeni, the demands of the Greek population who came from Trabzon, Gümüşhane and Ünye from the Black Sea for a long time re-choose Christiyanity are also seen in the documents. As the name suggests, Akdagmadeni has been an area of attraction due to the fact that mining is a region where stone workmanship exists.

Bu çalışma, 20.yüzyıl başında Ankara Vilayetine bağlı olan Yozgat Sancağının ve iki “büyük” kazası olan Boğazlıyan ve Akdağmadeni’nin coğrafi, tabii, sosyal, ekonomik ve idari durumunu ortaya koymayı amaçlamaktadır. Bu çerçevede çalışmanın ana kaynağını 1325 Numaralı Ankara Vilayeti Salnamesi ile Osmanlı Arşivi ve Cumhuriyet Arşivindeki belgeler oluşturmaktadır. Yanı sıra Yozgat tarihi ile ilgili bazı araştırma eserlerinden de yararlanılacaktır. Çalışmada Yozgat’ın 20.yüzyıl başında neredeyse bugüne benzer coğrafi ve tabii özelliklere sahip olduğu kaydedilmiştir. Nüfus ekseriyeti Müslümanlardan oluşmakla beraber gayrimüslim nüfusa hem merkezde hem de Salnamede yer verilen bu iki kazada da rastlanmaktadır. Rum nüfus özellikle Akdağmadeni bölgesinde daha çoğunluktadır. Yozgat Sancağı ve ilçelerinin ekonomik durumu, vergiler ile yetiştirilen hububat ve hayvancılık üzerinden kayıtlanmıştır. Özellikle Akdağmadeni’nde Karadeniz’den Trabzon, Gümüşhane ve Ünye’den uzun süre önce gelmiş Rum nüfusun askere gitmemek için tekrar Hristiyanlığı seçmeye dönük talepleri belgelerde görülmektedir. Akdağmadeni adından anlaşılacağı üzere madenciliğin, taş işçiliğinin olduğu bir bölge olması sebebiyle de çekim alanı olmuştur.
20.YÜZYIL BAŞINDA YOZGAT SANCAĞI İLE AKDAĞMADENİ VE BOĞAZLIYAN KAZALARININ COĞRAFİ, TABİİ, SOSYAL, EKONOMİK VE İDARİ DURUMLARI